COORDINATED HIGH LATITUDE EXPERIMENTS FOR THE SIMULATION OF NUCLEAR-BURST EFFECTS ON VLF SYSTEMS. - Banks, P. M.; Imhof, G. W.; Oelbermann, E. J.; Sechrist, C. F., Jr.; Volz, C., Jr. (1965)
This report describes some coordinated high latitude experiments which are being conducted for simulating nuclear-burst effects on long-range VLF propagation. The program consists of four parts: collection and study of VLF phase and amplitude data over four long range, high latitude VLF propagation paths; collection and study of ionospheric data (cosmic noise absorption data) near Reykjavik, Iceland; collection and study of other VLF ionospheric data from external sources (including satellite data); and study and comparison of items 1 through 3 with nuclear test VLF data. (Author)